Foreign women authors under Fascism and Francoism : gender, translation and censorship - Godayol, Pilar, 1968-; Taronna, Annarita, (Cambridge Scholars Publishing, 2018)
"This collection of essays highlights cultural features and processes which characterized translation practice under the dictatorships of Benito Mussolini (1922-1940) and Francisco Franco (1939-1975). In spite of the different timeline, some similarities and parallelisms may be drawn between the power of the Fascist and the Francoist censorships exerted on the Italian and Spanish publishing and translation policies. Entrusted to European specialists, this collection of articles brings to the fore the microhistory that exists behind every publishing proposal, whether collective or individual, to translate a foreign woman writer during those two totalitarian political periods. The nine chapters presented here are not a global study of the history of translation in those black times in contemporary culture, but rather a collection of varied cases, small stories of publishers, collections, translations and translators that, despite many disappointments but with the occasional success, managed to undermine the ideological and literary currents of the dictatorships of Benito Mussolini and Francisco Franco." -- Contraportada.